2022
DOI: 10.3389/fpsyg.2022.875646
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Leadership Challenges of K-12 Public Schools During COVID-19 Disruption: A Systematic Literature Review

Abstract: Globally, the COVID-19 pandemic is triggering a public health emergency and crisis on a large scale, with far-reaching effects and severe damage to all aspects of politics, economy, cultural and social life, and health. Consecutive outbreaks over the past nearly 2 years of “living with COVID-19” have forced most schools to physically close, resulting in the largest educational disruption in human history. In turbulent times of the COVID-19 crisis, school leaders are facing numerous major challenges germane to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
1
33
0
3
Order By: Relevance
“…As their findings revealed, English university teachers confirmed that CT should be an integral part of classroom teaching. In addition, it was also concluded in another recent study that CT and self-regulation give directions to teachers' preferred teaching styles (Heydarnejad et al, 2021b ; Parveen et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 89%
“…As their findings revealed, English university teachers confirmed that CT should be an integral part of classroom teaching. In addition, it was also concluded in another recent study that CT and self-regulation give directions to teachers' preferred teaching styles (Heydarnejad et al, 2021b ; Parveen et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 89%
“…COVID-19 has affected governments globally, and societies are experiencing an odd situation; after the global pandemic, this situation led to a global crisis that touched the aspect of our lives, including family, education, health, work, and the relationship between leaders and followers in our society (Hinojosa et al, 2020 ; Aslam et al, 2021 ; Parveen et al, 2022a ). Organization leaders play a critical role in framing employee experiences at the workplace during and after the pandemic as they adapt to work on new realities (Ngoma et al, 2021 ).…”
Section: Covid-19 and Leadershipmentioning
confidence: 99%
“…Recent research on leadership during disruptive times underscored critical areas that require special attention, including student mental health, staff morale, leadership capability, and the digital divide ( Harris and Jones, 2020 ; Parveen et al, 2022 ). To understand how school leaders build capacities to effect changes during the COVID-19 pandemic, the theoretical frameworks applied to this research study consist of four essential concepts: (a) Trauma-informed approaches to leadership, (b) transformative learning theory, (c) leadership through crisis management, and (d) digital equity.…”
Section: Literature Reviewmentioning
confidence: 99%